Análisis jurídico y el trabajo infantil en los niños, niñas y adolescentes - Vidal Hidalgo, Joselin Daniela (2025)
Child labor in Ecuador, particularly in Guayaquil, remains a significant social and legal issue. Despite progress in legislation and public policies, its persistence reflects the significant challenges in strengthening child protection processes to ensure compliance with the rights enshrined in the Constitution and the Code of the Child and Adolescent. This current study aims to examine the set of laws that regulate and sanction the work of children and young people in Guayaquil, identify the structural causes that perpetuate it, and evaluate the effectiveness of current regulations and public policies. Thus, strategies are proposed to strengthen its prevention and eradication. The work employs a hybrid research methodology, using qualitative and quantitative techniques. Current legislation will be reviewed, case studies will be conducted, and interviews with child rights experts will be conducted. In addition, surveys will be applied to the population and statistical analysis will be conducted to identify patterns and correlations. This methodology will allow for the generation of proposals based on normative, social, and statistical evidence, thus contributing to the gradual elimination of child labor, promoting comprehensive development in Ecuadorian children.